NGOs and social welfare : new research approaches - Lewis, David; Ravichandran, N. (Jaipur : Rawat Publications, 2008)
Contributed articles; chiefly with reference to South Asia.
Includes bibliographical references and index.
Keywords: NON-GOVERNMENTAL ORGANIZATIONS -- SOUTH ASIA; SOCIAL SERVICE -- SOUTH ASIA